Implementation of Mini Piles and Retaining Wall in the Construction of the North Kalimantan Provincial DPRD Building in Bulungan Regency - Hendi, Madrotin Noer; Liana, Ulwiyah Wahdah Mufassirin; Onaya, Gariel; Yatnikasari, Santi; Pitoyo, Pitoyo; Ilpandari, Ilpandari (JSE Journal of Science and Engineering, 2024)
Piles are used as the foundation for a building's construction when the underlying soil beneath the structure lacks sufficient bearing capacity to support the weight of the construction and its load, or when hard soil with enough bearing capacity lies at a significant depth. Retaining walls are a type of civil construction built to withstand the lateral active pressure of soil or water. Therefore, the construction of a retaining wall must be planned and designed to safely counter potential forces that could cause structural failure. The purpose of this writing is to understand the implementation of mini pile foundations and retaining walls concerning the stability control of the retaining wall against sliding, overturning, and soil-bearing capacity. The observational method used involves collecting secondary and primary data. The mini pile foundations are driven to a specified depth, with each pile segment being 4.0 meters long, and this piling activity aligns with the plan. The retaining wall used is a cantilever retaining wall with concrete quality K-300 f’c 25 MPa, where the successive heights, upper width, and bottom width of the retaining wall are 4.5 m, 0.3 m, and 2.7 m, respectively.